Regeneration of Heglig [Balanites aegyptiaca (Del)] west of the Blue Nile river within the short grass Savanna zone in the Sudan - Mustafa, Hasabelrasoul F.; Abaker, Mohamed A. (Gezira Journal of Agricultural Science, 2020)
Balanites aegyptiaca is a promising widely distributed tree of high value in terms of economic, social, and environmental issues, but it is neglected and not given full attention concerning its conservation. The objective of this study was to assess the regeneration of B. aegyptiaca west of the Blue Nile river within Acacia-Balanites vegetation zone in Sudan. A field experiment was carried out during the rainy season in 2015 in Nawara natural forest on its germination where viable fruits with intact or removed pericarp and mesocarp were buried at 0-cm and 5-cm depth in plots each surrounded by a metallic ring. Germinated fruits were counted weekly. An experiment on the effect of salinity on germination was performed, using both NaCl and CaCl to fix different levels of salinity in the clay soil. Number of germinated fruits was recorded weekly. Survey of the regeneration in the field was carried out in spot samples laid immediately after the rainy season at distinguished locations; abandoned agricultural farms, vicinity of the villages, crusted sites ( Karab ), valley meander and valley banks. In each location, three spot samples, 50 m in diameter each, were demarcated. All the B. aegyptiaca plants within the samples were calculated and their shoot height and diameter at ground level were measured. The soil moisture content in the five sites was measured in April, the driest month. The results revealed that fruits of B. aegyptiaca sown after the removal of both the pericarp and mesocarp or left them intact germinated readily when placed on the soil surface (91%) or buried to 5-cm depth (88%). Salinity significantly decreased the germination as it dropped from 83% on average at EC 0.8dSm -1 (control) to 36% at EC12 dSm -1 . B. aegyptiaca regenerated continuously on all the sites except on the valley bank and meander, where newly recruited natural regeneration was lacking. The study recommended more concern and attention to conserve B. aegyptiaca through improving management and extension programs and reserving lands as forests where the tree exists.   تعتبر شجرة الهجليج [ Balanites aegyptiaca (Del.)] ذات أهمية وقيمة اجتماعية واقتصادية وبيئية، وهي واسعة الانتشار، بيد أنها لم تجد الاهتمام والرعاية اللازمين مما يهدد وجودها وانتشارها. لذلك هدف هذا البحث إلى دراسة التجدد الطبيعي للشجرة غرب النيل الأزرق في الأراضي الجافة بالسودان، فيما يعرف بحزام الطلح والهجليج. لدراسة قدرة بذرة الهجليج على الإنبات نفذت تجربة في غابة نوارة الطبيعية في خريف العام 2015 وذلك بتقسيم ثمار الهجليج ، التي أنتجت في نفس العام ، إلى مجموعتين. تمت زراعة الثمار في المجموعة الأولى كما هي بدون إزالة القشرة الخارجية  واللب وفي الثانية أزيلت القشرة الخارجية واللب، وفي كلا المجموعتين كانت الزراعة على أعماق صفر و5 سم في مربعات أحيطت بحلقات حديدية بقطر 25 سم. تم حساب عدد الثمار التي نبتت بنهاية موسم الخريف. لمعرفة تأثير ملوحة التربة على إنبات ثمار الهجليج أستخدم نوعين من الأملاح هما كلوريد الصوديوم وكلوريد الكالسيوم للحصول على درجات ملوحة مختلفة في التربة الطينية. تم حساب عدد الثمار التي نبتت اسبوعيا لمدة خمسة أسابيع. تم تقويم التجدد الطبيعي لشجرة الهجليج في موقع البحث  في الأراضي الزراعية البور و الغابات الطبيعية المقطوعة و حمى القرى و الوديان وأراضي الكرب في عينات عشوائية قطر كلٍ منها 50 متراً. أحصيت في كل عينة نباتات الهجليج الموجودة مع قياس طول وقطر ساق لكل منها. حسبت نسبة رطوبة التربة في كل موقع في شهر أبريل من العام 2015. أثبتت النتائج أن القشرة الخارجية واللب وكذلك عمق التربة لا تؤثر على إنبات الثمار حيث أنبتت ثمار الهجليج مزالة القشرة الخارجية واللب  وتلك التي لم تزال منها القشرة الخارجية واللب مباشرة عند زراعتها عند عمق صفر(91%) أو 5 سم (88%). خلصت الدراسة كذلك إلى أن زيادة نسبة الملوحة في التربة تقلل من نسبة إنبات ثمار الهجليج في كلا النوعين من الأملاح المستخدمة، حيث تدنت نسبة الإنبات من 83% عند أدنى مستوى ملوحة 0.8 دسم -1 (الشاهد) إلى 36% عند أعلى مستوى ملوحة 12 دسم -1 . أشارت النتائج أيضاٍ إلى أن الهجليج تجدد طبيعياً تجدداً متواتراً في كلا المواقع باستثناء مجاري وضفاف الوديان حيث كان التجدد غير متواتر. توصي الدراسة بضرورة إيلاء الاهتمام والرعاية اللازمين للمحافظة على الشجرة من خلال تحسين وتطوير نظم الإدارة وتكثيف برامج الإرشاد وغرسها كغابات محجوزة.